Long‐Term Dosing of Intrathecal Baclofen in the Treatment of Spasticity After Acquired Brain Injury. Issue 6 (8th January 2017) - Maneyapanda, Mithra B.; McCormick, Zachary L.; Marciniak, Christina; Reger, Christopher
Abstract: Background: Intrathecal baclofen (ITB) often is used to treat severe spasticity of cerebral origin. Although literature exists regarding the efficacy of ITB, there has been minimal investigation related to dosing in the adult‐acquired brain injury population, particularly at long‐term duration. Objective: To investigate long‐term dosing of ITB in adult patients with spasticity of cerebral origin due traumatic brain injury (TBI), stroke, and hypoxic‐ischemic encephalopathy (HIE). Design: Retrospective cohort study. Setting: An academic outpatient rehabilitation clinic. Patients: Forty‐two adult patients with spasticity secondary to TBI, stroke, or HIE treated with ITB for greater than 3 years. Methods: Medical records and device manufacturer records of included patients were reviewed to obtain demographic data, dosing information, dates of pump and catheter placements, and revisions. Main Outcome Measure: Average daily ITB doses and mean change in ITB dose over 1, 2, and 3 years. Goal of ITB treatment (active function versus comfort/care/positioning) also was compared. Results: Of 42 total patients, spasticity was attributed to either TBI (n = 19), stroke (n = 11), or HIE (n = 12). The mean (standard deviation) age was 35.21 (10.17), 56.7 (13.1), and 35.1 (12.4) years for the TBI, stroke, and HIE groups, respectively ( P < .001). There was a significant difference in the goal of therapy with "improving functional independence, " accounting for 27.8%, 72.8%, and 0% in the TBI, stroke, and HIE groups, respectively ( P = .002). The mean duration of ITB therapy was 8.5 (5.0), 7.8 (3.4), and 9.1 (4.6) years in the TBI, stroke, and HIE groups, respectively ( P = .79). The mean daily ITB dose was 596.9 (322.8) μg/d, 513.2 (405.7) μg/d, and 705.2 (271.7) μg/d for the TBI, stroke, and HIE groups, respectively ( P = .39). In the subset of the cohort with ITB therapy for more than 5 years, the mean percent change in daily ITB dose between time of chart review and 1, 2, and 3 years previously was 7.3% (13.6), 12.7% (16), and 24.7% (50.3), respectively. A complex dosing pattern was used more frequently in those with stroke (36.4%) compared with the TBI and HIE (9.7%) groups ( P = .04). Conclusion: Despite the long‐term use of ITB therapy in this cohort, the mean daily dose of ITB continued to require adjustments. There was no significant difference in the mean daily dose between patients with a diagnosis of TBI, stroke, or HIE. A complex dosing pattern was used more frequently in patients with stroke. Level of Evidence: III